Charge-Transfer Modeling and Polarization DRT Analysis of Proton Ceramics Fuel Cells Based on Mixed Conductive Electrolyte with the Modified Anode–Electrolyte Interface - Wang, Xinxin; Ma, Zhenkai; Zhang, Teng; Kang, Jianhong; Ou, Xuemei; Feng, Peizhong; Wang, Shaorong; Zhou, Fubao; Ling, Yihan (ACS applied materials & interfaces, 2018)
A charge-transfer model considering the mixed conductivities of proton, oxygen ion, and free electron in interface-modified La2Ce2O7 (LCO) electrolyte is designed to analyze the characteristics of proton ceramics fuel cell in the field of the open-circuit voltage, internal short-circuit current, proton-transfer number, discharging curves, oxygen/hydrogen partial pressure, and cell efficiencies. The properties of anode-supported single cells with the modified anode–electrolyte interface containing an in situ formed doped BaCeO3 reaction layer are compared to those of unmodified cells at various temperatures T and H2O partial pressures. Besides, the electrochemical impedance spectroscopies of both cells were investigated by the relaxation time distribution to distinguish different polarization processes. The results indicated that the reaction interface layer can effectively reduce the internal short-circuit current density and increase the proton-transfer number of electrolytes. Importantly, the NiO–BaZr0.1Ce0.7Y0.2O3‑δ anode can also make more protons transfer from anode to cathode and participate in the cathodic reaction for LCO-based proton ceramics fuel cell. The polarization of the cell decreases with the increase of water partial pressure, which leads to the increase of open-circuit voltage and cell efficiency.